Linguistic and cultural cognitive relevance of televised narratives to the Ndebele child in Bulawayo - Nhongo, Raphael (Stellenbosch University, 2022)
This paper focuses on narratives that are transmitted through South African Broadcasting Commission (SABC) television to the people of Zimbabwe, particularly children with Ndebele as their first language. Today, mainly in towns and cities, children no longer listen to folktales from grandmothers at home as the television has taken over that role. Because the Ndebele and Zulu languages are similar through being Nguni languages, most Ndebele people have resorted to SABC television as the Zimbabwe Broadcasting Corporation offers more programmes in Shona than in Ndebele. This paper traces the relevance of Zulu, which is the language used in the transmission and the Zulu culture which is contained within children’s tales, particularly in YoTV Land, to the cognitive development of a child whose first language is Ndebele. Forty children were selected from two primary schools in Bulawayo as research participants to investigate how they are linguistically and culturally influenced by South African television. The paper ends by showing how narratives are influential in the cognitive development of a child and how the cognitive growth of a child who is exposed to two similar but different cultures and languages may be affected. The major effect is that those children who are below the age of nine years may not get the message being conveyed in the narrative since they have not been adequately exposed to linguistic and cultural variation and diversity.